Changes in the position and inclination of the upper incisor and upper lip postorthodontic treatment: case reports - Chacón Moreno, Alicia (2023)
Objective: To determine the changes in the position and inclination of the upper incisor and upper lip after orthodontic treatment in a series of 3 clinical cases. Materials and Methods: The three reported clinical cases correspond to adult patients who were treated with fixed orthodontics and premolar extractions. Measurements of upper incisor position (UIP), upper incisor inclination (UII), upper lip position (ULP), and upper lip inclination (ULI) were performed on pre-treatment and post-treatment cephalometric radiographs for assessment of changes. Results: In the first case a variation of -1 mm was found for both the UIP and the ULP, as well as a variation of the UII and the ULI, although in different magnitude. Case 2 presented a 2 mm variation in the UII with minimal changes in the upper lip (Δ ULP = 0 mm and Δ ULI =-0.5 mm) and in case 3 a 2 mm variation was obtained for both IIS and ILS. Conclusions: The results obtained in this case reports show us a wide variability, so it is impossible to accurately predict changes in soft tissues as a response to tooth movement. Clinical significance: Predicting tooth movement changes in soft tissues is critical during the initial planning phase of orthodontic treatment.